Aberrant Methylation of Preproenkephalin and p16 Genes in Pancreatic Intraepithelial Neoplasia and Pancreatic Ductal Adenocarcinoma - Fukushima, Noriyoshi (American Society for Investigative Pathology, 2002)
Pancreatic intraductal neoplasia (PanIN) is thought to be the precursor to infiltrating pancreatic ductal adenocarcinoma. We have previously shown that the preproenkephalin (ppENK) and p16 genes are aberrantly methylated in pancreatic adenocarcinoma. In this study we define the methylation status of the ppENK and p16 genes in various grades of PanINs. One hundred seventy-four samples (28 nonneoplastic pancreatic epithelia, 7 reactive epithelia, 29 PanIN-1A, 48 PanIN-1B, 27 PanIN-2, 14 PanIN-3, 15 invasive ductal adenocarcinomas, and 6 miscellaneous pancreatic neoplasms) were microdissected from 29 formalin-fixed paraffin-embedded surgically resected pancreata, and were analyzed by methylation-specific polymerase chain reaction. Fourteen of 15 (93.3%) invasive pancreatic ductal adenocarcinomas showed methylation of the ppENK gene and 4 of 15 (26.7%) showed methylation of the p16 gene. Nonneoplastic pancreatic epithelia did not harbor methylation of either gene. The prevalence of methylation of the ppENK gene increased significantly with increasing PanIN grade. A similar nonsignificant trend was noted for p16 methylation. Aberrant methylation of the ppENK gene was found in 7.7% of PanIN-1A, 7.3% of PanIN-1B, 22.7% of PanIN-2, and 46.2% of PanIN-3. Aberrant methylation of the p16 gene was found in 12% of PanIN-1A, 2.6% of PanIN-1B, 4.5% of PanIN-2, and 21.4% of PanIN-3. All but one of the PanINs from the 14 pancreata without pancreatic carcinoma was unmethylated with respect to either the p16 or ppENK gene. Our results suggest that methylation-related inactivation of the ppENK and p16 genes is an intermediate or late event during pancreatic carcinogenesis. Because aberrant methylation of ppENK or p16 was more often detected in similar grade PanINs from patients with pancreatic carcinoma than in those with other pancreatic diseases, it may be a useful indicator of the potential malignancy of epithelial cells of the pancreas.